Construction of road at Desa Bangau Parit, 28000 Temerloh, Pahang Darul Makmur / Nur Hidayah Rahim - Rahim, Nur Hidayah (Universiti Teknologi MARA, Perak, 2018)
A road is very important to the living to undergo their daily life as they will be using the road to transport from one place to another place. Therefore, this report will discuss about how the construction of road was conducted at construction site. This case study was conducted in Desa Bangau Parit, Temerloh Pahang Darul Makmur. The purpose of this report is to study the method construction of the road. Besides, this report contains the factors to be considered in constructing the road, along with the problems and solutions to the road works. Every construction must be accompanied by a few problems, so it is very important to have knowledge as it will help to solve any problems that are coming on the spot.